Electrochemical Application of Structured Color Nanotextile Materials in Garment Design - Zekai Zhang (Journal of Chemistry)
In order to improve the color saturation of textile structured chromogenic photonic crystals, this paper proposes that the dye adsorbed PSt structural elements (reactive dyes/PSt microspheres) on the outer surface can be used to construct electrochemically structured chromogenic photonic crystals on mulberry fabrics by digital printing. In this method, the adsorption conditions and adsorption model of dyes on the surface of PSt colloidal microspheres were studied. The structure and morphology of reactive dyes/PSt microspheres, the arrangement of the obtained photonic crystals, and the structural chromogenic effect were characterized. The results showed that the amount of dye adsorbed on the surface of microspheres increased significantly with the increase of adsorption temperature from 25°C to 65°C. When the adsorption temperature continued to rise to 75°C, the dye adsorption capacity on the surface of PSt microspheres did not increase significantly. The adsorption model accords with the Langmuir model; reactive dye/PSt microspheres have a typical core-shell structure, and the particle size of the microspheres is slightly larger than that before adsorption. Conclusion. The reactive dye/PSt photonic crystal chromogenic electrochemical structure constructed on the surface of white silk fabric has a regular and orderly arrangement of microspheres, showing bright structural color.